Utilization of Food Waste with Cow Manure as a Co-Substrate for Electricity Generation - Juan Vincent; Aussie Amalia; Praditya sigit Ardisty Sitogasa (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
Food waste is the dominant component of organic waste generation in Indonesia and drives environmental pollution via greenhouse gas release, particularly methane. This research is conducted to examine the potential of food waste as a biogas feedstock, the influence of the influence of different ratios of food waste and cattle manure on methane yield (CH₄) production, and assess the potential conversion of biogas into electrical energy using a Thermoelectric Generator (TEG). The research was conducted on a laboratory scale using a 15 L batch-type anaerobic digester with food waste to cattle manure ratios of 50:50 and 74:26. The analyzed parameters included C/N ratio, pH, temperature, methane concentration, biogas volume, and electrical power generated from thermal energy conversion through biogas combustion using a SP1848 Thermoelectric Generator. The results indicate that substrate composition significantly affects fermentation pH stability, temperature, and methane content, with certain compositions producing higher CH₄ percentages and greater potential for electricity generation. Although the energy conversion efficiency of the Thermoelectric Generator remains relatively low, this study demonstrates that food waste has promising to be developed as a sustainable alternative energy resource and can contribute to sustainable waste management and environmentally friendly energy production.